Permacultura para el diseño sostenible de vivienda de interes prioritario, dirigida a personas en estado vulnerabilidad del barrio República de Canadá. (2022)
In the peripheral areas there are urbanized areas in a fragmented manner by informal housing clusters given by the need of families in a state of socioeconomic vulnerability and the easy acquisition of land (Cuellar, 2018); there is evidence of a development given by self-construction within the public space and the conformation of housing belonging to the classification of slums, which present scenarios of informality, where they are linked to factors of precariousness, in terms of poverty, lack of resources, dependence on the center and vulnerability reflected by the risks and threats that affect the population in environmental, economic, social spheres or the minimum or nonexistent conditions of habitability (UN-habitat,2014).